Implementasi Logbook Kompetensi Perawat Berbasis Digitalisasi - Lusia Dian Wahyu Winarti; Tuti Afriani; Dudi Mashudi (Journal of Telenursing (JOTING), 2023)
This research aims to identify problems and find solutions for nurses in providing proof of competency through a digitalization-based competency logbook. The study used a case report approach with interviews and distributed questionnaires in the ER (Emergency Department) to 103 nurses to implement digitalization-based competency logbook innovation. The research results show a competency logbook (SOP) (Standard Operational Procedure), a digitized logbook operational flow, a competency logbook link, and a spreadsheet link have been prepared. Logbook implementation and performance evaluation: 81.5% of IGD nurses apply digitalization-based competency logbooks. In conclusion, digitalization-based competency logbooks are an effort to resolve problems related to the sub-optimality of nurse competency logbooks. Keywords: Digitalization, Competency Logbook, Nurse